MANAGEMENT OF TRADITIONAL PESANTREN IN CULTIVATING STUDENTS' ENTREPRENEURIAL BEHAVIOR - Tosuerdi, Tosuerdi; Mulyanto, Agus; Holik, Abdul (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This article examines the management patterns of pesantren salaf, pesantren Kanzul Ulum and an-Nida are as a sample, in fostering entrepreneurial behavior among students. This research applies a qualitative approach, which provides an in-depth picture of the actual situation in the field. This research uses the theory of four management functions; Planning, Organizing, Actuating and Controlling. Pesantren have a rich collective scientific heritage. So far, pesantren have prepared the younger generation in various aspects of life, including agriculture, as a symbol of their preparation for the outside world. However, currently, the focus of these preparations has shifted to entrepreneurship, considering its important role in the current global economy. The research results show that Pesantren need to strengthen their identity as Islamic educational institutions before including the field of entrepreneurship into the curriculum. The implementation of a curriculum that is integrated with entrepreneurship needs to be supervised by Islamic boarding school administrators to maintain the Islamic integrity of students in the world of entrepreneurship. The aim is to create students who are competent in the field of entrepreneurship without being trapped in purely material interests.